Pengembangan Ekonomi Kreatif Melalui Pelatihan Pembuatan Produk Totebag Ecoprint dengan Teknik Pounding pada Siswa Kelas VII SMP Negeri 25 Oku Desa Lubuk Banjar - Maulidya, Zakyatul; Dwijayanti, Fitri; Jida, Citra Roza; Dhany, Andyka Rama; Dawara, Arga; Mardalena, Erfin (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The development of education-based creative economy is one of the strategic efforts to instill entrepreneurial spirit from an early age. This study aims to describe the process and results of producing tote bags using the ecoprint technique by pounding as a means of developing creative economy among seventh grade students at SMP Negeri 25 OKU, Lubuk Banjar Village. The research method used a descriptive qualitative approach through practical activities, observation, and documentation. Data analysis techniques were carried out through data reduction, data presentation, and descriptive conclusions. The results of the study indicate that ecoprint activities can increase student creativity, motor skills, understanding of the economic value of products, and interest in entrepreneurship. The ecoprint tote bags produced have aesthetic value and sales potential, thus serving as a contextual learning medium that supports the development of school-based local creative economy.